1975
DOI: 10.1042/bj1510051
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of Pseudomonas aeruginosa cytochrome c oxidase with carbon monoxide

Abstract: The binding of CO to ascorbate-reduced Pseudomonas cytochrome oxidase was investigated by static-titration, stopped-flow and flash-photolytic techniques. Static-titration data indicated that the binding process was non-stoicheiometric, with a Hill number of 1.44. Stopped-flow kinetics obtained on the binding of CO to reduced Pseudomonas cytochrome oxidase were biphasic in form; the faster rate exhibited a linear dependence on CO concentration with a second-order rate constant of 2 X 10(4) M-1-s-1, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 16 publications
6
37
0
1
Order By: Relevance
“…The present kinetic results do not allow us to say which haem, c or dl, is the binding site for oxygen, but ligand-binding evidence (Parr et al, 1975;1978 . This behaviour would therefore appear to parallel that of mammalian cytochrome c oxidase (Gibson et al, 1965;Greenwood & Gibson, 1967), in which the presence of the substrate, oxygen, greatly increased the electron-transfer rates within the protein, although it is clear that the rate of oxygen reduction by the bacterial enzyme is very much lower than that…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The present kinetic results do not allow us to say which haem, c or dl, is the binding site for oxygen, but ligand-binding evidence (Parr et al, 1975;1978 . This behaviour would therefore appear to parallel that of mammalian cytochrome c oxidase (Gibson et al, 1965;Greenwood & Gibson, 1967), in which the presence of the substrate, oxygen, greatly increased the electron-transfer rates within the protein, although it is clear that the rate of oxygen reduction by the bacterial enzyme is very much lower than that…”
Section: Discussionmentioning
confidence: 74%
“…Ligand-binding studies on the reduced enzyme have shown that both CO and cyanide bind to the haem d1 component (Parr et al, 1975;, and on this basis it has been assumed that this particular redox centre is also the site of attack by oxygen. Two previous attempts at understanding the detailed mechanism of the reaction of Pseudomonas cytochrome oxidase with oxygen have been reported. Shimada & Orii (1976) have used rapid-scanning spectrophotometry to observe the reduction of the enzyme by excess ascorbate in the presence of oxygen.…”
mentioning
confidence: 99%
“…The kinetics of NO release from the fully reduced NO-bound wild type cd 1 NIR is biphasic with values of 35 and 6 s Ϫ1 at pH 7.0 (average from values listed in Table 1). Although the biphasicity is not understood at present, it might be related to the dimeric structure of the enzyme, which has been previously shown to display cooperative behavior with some ligands, such as CO (20) and cyanide (24). An intrinsic functional asymmetry of the enzyme is also evident in the reaction with macromolecular electron donors (such as azurin and cytochrome c551) (27,28) and in the intramolecular electron transfer step (29).…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49] Many date from the days when the enzyme was referred to as "bacterial cytochrome oxidase", because of its ability to reduce O 2 to water (albeit much more slowly than mammalian cytochrome c oxidase) and the presence of four electron acceptor groups per dimer. These studies were aimed at exploring the relationship between the bacterial and mammalian cytochrome oxidases.…”
Section: A Heme CD 1 -Containing Nitrite Reductasesmentioning
confidence: 99%